A dual-benchmark based energy analysis method to evaluate control strategies for building HVAC systems. (1st December 2016) - Du, Zhimin; Jin, Xinqiao; Fang, Xing; Fan, Bo
Highlights: Dual-benchmark based operation efficiency evaluation method is presented for HVAC systems. A control-perfect index based exergy analysis method is presented. Ideal operation level is searched out through minimizing the system exergy loss. Energy saving ratio and improving potentials of various control strategies are evaluated. Abstract: Optimal control strategies have been increasingly developed in heating, ventilation and air conditioning (HVAC) systems. The commonly used evaluation method, which compares the system's energy consumption under proposed strategy with that under its original control, has several limitations. A dual-benchmark based CPI (control-perfect index) evaluation method is presented to assess the operation of an airport HVAC system under various control strategies. Firstly, the exergy loss models based on the HVAC productive structure are developed to analyze the exergy efficiency of component and system. Secondly, control-perfect index based on the process exergy analysis is presented as an evaluation factor for the operation of HVAC system. In addition, the original control of system is used as the 1st benchmark to estimate the energy saving capacity of proposed strategy. The ideal operation, which is obtained through the global optimization of exergy loss models, is used as the 2nd benchmark to estimate the improving potential of candidate strategy. Finally, twelve control strategies used in the airport HVAC system are evaluated through the CPI analysis of both component and system. Their energy saving ratios to Benchmark 1 and improving potentials to Benchmark 2 are compared, respectively.